From Memory to History Television Versions of the Twentieth Century - Cullen, Jim (Rutgers University Press, 2021)
"History is a subject we all learn in school, some of us with more enthusiasm than others. But the way most of us know history-experience it, absorb it, apply its lessons to make sense of our everyday lives-is through popular culture. And no medium of popular culture has been more pervasive in offering Americans a vision of their country in the past century than television. Television has played an especially important role in the interpretation-and reinterpretation-of collective memory, which is to say the events that were experienced first- or second-hand but which have since receded into the past. From Memory to History examines the way TV shows of the past fifty years have depicted US society in the last century. The book examines how a series of events in the past hundred years-from the advent of Prohibition to the advent of the Internet-were portrayed in some of the most beloved shows of all time, among them The Waltons, M*A*S*H, and Mad Men. But the book does more than that. It also explains how any given TV show is at least as important a historical artifact of the time it was made as it is the time it depicts. So it is, for example, that we see how That ''70 Show reveals a lot about the 1990s in the process of telling a story about the 1970s. Or How Hogan's Heroes, a (somewhat bizarre, in retrospect) sitcom about a German concentration camp in World War II, almost despite itself, reveals underlying anxieties about Civil Rights and the Vietnam War in its hermetically sealed episodes. Or how The Americans valorizes the outcome of a Cold War that was a good deal more uncertain than it was in the 1980s, when the series is set. Each of the book's seven chapters offers context for a show's setting, the show's interpretive argument in the moment it was made, and how both look from the perspective of the 2020s. Here, truly, is history in three dimensions. Lively, informative, and incisive, From Memory to History will help you look at television, the American Century, and the times in which you are living in an intriguing new light"--